Mass Media and Society - Curran, James; Gurevitch, Michael (London : Hodder Arnold, 2005)
In this well established text, a team of international scholars give their thoughts on mass media and culture. The book also seeks to reflect changing emphasis in the study of mass communication and popular culture
Section I. Media and society: general perspectives. Critical debates in Internet studies: reflections on an emerging field / Sonia Livingstone ; Feminism without men: feminist media studies in a post-feminist age / Karen Boyle ; Representation, reality and popular culture: semiotics and the construction of meaning / Christine Geraghty ; Culture, communications and political economy / Graham Murdock, Peter Golding ; Globalization and national media systems: mapping interactions in policies, markets and formats / Kalyani Chadha, Anandam Kavoori ; Rethinking the study of political communication / Jay G. Blumler, Michael Gurevitch ; Mediations of democracy / James Curran -- Section II. Media systems, organizations and cultures. The production of media entertainment / David Hesmondhalgh ; Four approaches to the sociology of news / Michael Schudson ; The culture of journalism / Barbie Zelizer ; Comparing media systems / Daniel C. Hallin, Paolo Mancini ; Media policy in the Middle East: a reappraisal / Naomi Sakr ; Media and democracy without party competition / Robert M. Entman ; Selling neo-imperial conflicts: television and US public diplomacy / Daya Kishan Thussu -- Section III. Media representations, mediations and influence. The information society debate revisited / Nicholas Garnham ; Comparative ethnography of new media / Daniel Miller, Don Slater ; National prisms of a global 'media event' / Chin-Chuan Lee [and others] ; Women and race in feminist media research: intersections, ideology and invisibility / Linda Aldoory, Shawn J. Parry-Giles ; Viewing and reviewing the audience: fashions in communication research / Tamar Liebes ; Political communication in a changing world / Peter Dahlgren, Michael Gurevitch
Includes bibliographical references and index.
Keywords: Mass media -- Social aspects; Mass media -- Political aspects